Robust ferromagnetic insulating and large exchange bias in LaMnO3:CoO composite thin films. (12th May 2022) - Zhang, Xiao-Yu; Tao, Ya-Jun; Jiao, Pei-Jie; Wang, Jian; Zhang, Ji; Luo, Zhen-Lin; Gu, Zheng-Bin; Zhou, Jian; Chen, Y B; Zhang, Shan-Tao
Abstract: Ferromagnetic insulators (FMIs) have received widespread attention for applications in novel low power consumption spintronic devices. Further optimizing robust ferromagnetic insulation and developing a multifunctional FMI by integrating other magnetic properties can not only ease or pave the way for actual application but also provide an additional degree of freedom for device design. In this work, by introducing antiferromagnetic CoO into the FMI LaMnO3, we constructed (1 − x )LaMnO3 : x CoO composite thin films. The films simultaneously show robust FMI characteristics and a large exchange bias (EB). For the x = 0.5 sample, the resistivity is 120 Ω cm at 250 K, the magnetization is 100 emu cm −3, and the EB field is −2200 Oe at 10 K. In particular, the blocking temperature is up to 140 K. Synchrotron radiation x-ray absorption spectroscopy reveals the coexistence of Mn 3+, Mn 2+, Co 2+ and Co 3+, arising from interfacial charge transfer and space charge/defect trapping, which should be responsible for the enhanced and integrated multifunctional magnetic properties.